Caracterização química e molecular de quatro espécies de Vitex (Lamiaceae) e bioatividade contra o ácaro-da-necrose-do-coqueiro Aceria guerreronis (Acari : Eriophyidae) - Barreto, Ighor Costa (2017)
Aceria guerreronis keifer is one of the main coconut pests in Brazil, its attack causes a premature fall, reduction of fruit size, water weight and volume, as well as stetic esthetic damages (necrosis) depreciating the product. Currently, there are five pesticides registered for the control of the coconut-necrotic mite. However, there is no specificity to A. guerreronis. The Lamiaceae family stands out with some specimens with notable insecticidal activity, among them the Vitex genus, known to have ecdysteroids and iridoids as markers of the genus. However, there is a shortage of specific chemotaxonomic studies for volatile compounds. The objective of this work was to identify the volatile compounds present in the essential oils of the species of Vitex gardneriana Schauer, Vitex capitata Vahl., Vitex rufescens A. Juss., Vitex megapotamica (Spreng.) Moldenk and to evaluate possible effects of toxicity and repellence against A. guerreronis. In addition to analyzing the genetic diversity of species of the genus Vitex using ISSR markers, verifying the occurrence of statistical correlations between the genetic diversity and the chemical profiles of the essential oils. Chromatographic and spectroscopic techniques (GC-MS / FID) were used for the detection of volatile compounds, and the molecular markers of ISSR for the genetic characterization of the species, as well as toxicity and repellency tests against necrotic necrosis. The results showed 46, 45, 41 and 37 constituents for V. capitata, V. megapotamica, V. gardneriana and V. rufences respectively, among which, -copaene, (E)-caryophyllene, -elemene, -humulene, trans-cadine-1(6)4-diene, viridiflorene and -cadinene were the main components of V. capitata and V. megapotamica. 6,9-guaiadiene, caryophyllene oxide, L-calamenene for V. gardneriana and (E)-cariophylene, ledol, germacrene D, -humulene, allo-aromadendrene, viridiflorene and -elemene for V. rufences. The results of molecular markers of ISSR generated a total of 90 fragments, of which 100% were polymorphic. The genotypes of the four Vitex species selected for this study were pooled using the Jaccard coefficient (JC). The mean similarity was 0.21 JC (0.08-0.45 JC). A clear separation of two groups was observed, with V. gardneriana being the most isolated of the four species, and V. capitata and V. megapotamica more closely related to each other. The acaricide activity of the four oils was also evaluated by means of toxicity and repellency tests against A. guerreronis. The essential oil of V. gardneriana showed acaricidal activity against A. guerreronis with a LC50 of 0.85 mg.mL-1, whereas the oils of V. capitata, V. megapotamica and V. rufecens were not toxic to this pest up to 2.3 mg. Ml-1 when tested through the toxicity bioassay. In general, essential oils distilled from the Vitex species repelled A. guerreronis after 24 hours at a concentration of 1.8 mg.mL-1 using abamectin as a control in the two-choice disc repellency assay, however, the essential oil of V. gardneriana presented a statistically significant acaricidal activity against the coconut mite necrosis. Introducing himself as a potential candidate for the development of an acaricide product.